2015
DOI: 10.1002/cncr.29563
|View full text |Cite
|
Sign up to set email alerts
|

Effects of melatonin on physical fatigue and other symptoms in patients with advanced cancer receiving palliative care: A double‐blind placebo‐controlled crossover trial

Abstract: BACKGROUND:Patients with advanced cancer often experience fatigue and other symptoms that negatively impact their quality of life. The current trial investigated the effect of melatonin on fatigue and other symptoms in patients with advanced cancer. METHODS: Patients who were aged 18 years, had a histologically confirmed stage IV cancer (TNM Classification), and who reported feeling significantly tired were recruited from the palliative care unit at the study institution. The study was a double-blind, randomiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 45 publications
0
45
0
Order By: Relevance
“…In 11 trials, some of the data needed for meta-analysis were not published in the trial paper; therefore, we sought contact with authors. We retrieved the necessary information from four of the 11 studies, making the number of trials available for quantitative analysis 2322–29 31–34 39 41–47 49–51 (online supplementary material for details on rejected articles).…”
Section: Resultsmentioning
confidence: 99%
“…In 11 trials, some of the data needed for meta-analysis were not published in the trial paper; therefore, we sought contact with authors. We retrieved the necessary information from four of the 11 studies, making the number of trials available for quantitative analysis 2322–29 31–34 39 41–47 49–51 (online supplementary material for details on rejected articles).…”
Section: Resultsmentioning
confidence: 99%
“…mortality, tumor remission, etc.) [40][41][42]. Accordingly, two meta-analyses demonstrated benefits of melatonin as an adjuvant to ameliorating radio chemotherapy-related side effects (i.e., asthenia, nausea and vomiting, hypotension, and thrombocytopenia), and improvement of tumor remission and survival [43,44].…”
Section: Discussionmentioning
confidence: 99%
“…However, a double-blind, placebo-controlled study reported that short-term melatonin treatment did not produce any significant influence on the estradiol and IGF-1/IGBBP-3 levels in women with a prior history of stages 0-III breast cancer [198]. Furthermore, another double-blind placebo-controlled crossover trial which included 72 patients suggested that 20 mg oral melatonin administration was not able to improve fatigue or other symptoms in patients with advanced cancer [199]. …”
Section: Clinical Trialsmentioning
confidence: 99%